Peningkatan Pengetahuan Kader Kesehatan mengenai Program Persiapan Persalinan dan Pencegahan Komplikasi (P4K) di Kecamatan Gumukmas - Sultanah Zahariah (Journal of Health Innovation and Community Services, 2022)
Background: Maternal mortality rate in the region of East Java has increased in 2020 namely 98,39/100.000 KH. Jember has the highest of maternal mortality rate in the East Java, which is 173,53/100.000 KH. Maternal mortality can occur either during pregnancy, childbirth or the puerperium period. Gumukmas is one of district in Jember which has a percentage of birth assisted by health workers as much as 98,2%, which means that there are still 1,8% of mother who gave birth not assisted by health provider. Kader as part of the community that close to pregnan women are expected to be able yo take a role in the implementation of the Childbirth Planning and Camplications Prevention Program (P4K). The aim of this study is to improve the kader’s ability to provide information to pregnant women about preparation for childbirth in Gumukmas. Method: the method that used is counseling by evaluating the increase of kader’s knowledge through pre and posttest questionnaire.Result: the result was found that 88% of kader have increase of knowledge in childbirtg preparation program and prevention of complication, 12 % have the same knowledge, and there were no participants with decrease of knowledge. This shows that the counseling carried out is quite efficient. Suggestion This result is expected to increase the ability of kader in providing education to pregnant women and families in preparing safety deliveries